Microsoft Windows workflow foundation 4.0 cookbook : over 70 recipes with hands-on, ready-to-implement solutions for authoring workflows /: over 70 recipes with hands-on, ready-to-implement solutions for authoring workflows. (2010) - Unknown
No abstract available